2010
DOI: 10.1017/s1751731109990917
|View full text |Cite
|
Sign up to set email alerts
|

Methionine-hydroxy analogue was found to be significantly less bioavailable compared to dl-methionine for protein deposition in growing pigs

Abstract: When methionine (Met) is limiting in swine diets, it is commonly supplemented by using anhydrous DL-methionine (DLM, 99% purity) or liquid DL-methionine-hydroxy analogue free acid (MHA-FA, 88% purity). The objective of this experiment was to test the null hypothesis that the bioavailability of DLM and MHA-FA were not different for growing pigs, using the indicator amino acid (AA) (phenylalanine, Phe) oxidation (IAAO) method in a slope-ratio assay. Six barrows (mean BW during study: 21.1 kg) received seven diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…In addition, circulating DAO activity is a useful indicator of intestinal permeability and mucosal injury (Li, Lu, Hu, Sun, & Yao, ). The present results found that L ‐Met had the potential to attenuate the increased activity of plasma DAO in the IUGR piglets, indicating that L ‐Met treatment is more effective in improving the morphological development of intestinal mucosa, which may be associated with the difference in relative bioavailability of the Met sources (Opapeju et al, ; Shoveller et al, ; Zimmermann et al, ).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In addition, circulating DAO activity is a useful indicator of intestinal permeability and mucosal injury (Li, Lu, Hu, Sun, & Yao, ). The present results found that L ‐Met had the potential to attenuate the increased activity of plasma DAO in the IUGR piglets, indicating that L ‐Met treatment is more effective in improving the morphological development of intestinal mucosa, which may be associated with the difference in relative bioavailability of the Met sources (Opapeju et al, ; Shoveller et al, ; Zimmermann et al, ).…”
Section: Discussionmentioning
confidence: 66%
“…Methionine (Met) is considered as the third‐limiting amino acid in the diets of pigs that must be supplied in adequate amounts to optimize performance (Brosnan, da Silva, & Brosnan, ; Gaines et al, ; Shoveller, Moehn, Rademacher, Htoo, & Ball, ). Methionine has the capacity to improve tissue development, promote antioxidant capacity and regulate immune function in animals (Liu, Zong, Zhang, & Cao, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linear models have been extensively used to determine bioavailability of individual amino acids or minerals in poultry (Major & Batterham ; Batterham, Lowe, Darnell & Major ; Adeola ; Parsons, Zhang & Araba ; Lumpkins & Batal ), pigs (Batterham, Andersen, Baigent & White ; Adeola , ; Fanimo, Susenbeth & Sudekum ; Mateo, Spallholz, Elder, Yoon & Kim ; Shoveller, Moehn, Rademacher, Htoo & Ball ; Petersen, Pedersen, Lindemann & Stein ), and recently, in fish (Zarate & Lovell ; El‐Haroun & Bureau ; Li, Burr, Wen, Goff, Murthy & Gatlin III 2009; Li, Wang, and Gatlin ;Poppi et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Linear models have been extensively used to determine bioavailability of individual amino acids or minerals in poultry (Major & Batterham 1981;Batterham, Lowe, Darnell & Major 1986; Adeola (Batterham, Andersen, Baigent & White 1990;Adeola 1996Adeola , 2009Fanimo, Susenbeth & Sudekum 2006;Mateo, Spallholz, Elder, Yoon & Kim 2007;Shoveller, Moehn, Rademacher, Htoo & Ball 2009;Petersen, Pedersen, Lindemann & Stein 2011), and recently, in fish (Zarate & Lovell 1997;El-Haroun & Bureau 2007;Li, Burr, Wen, Goff, Murthy & Gatlin III 2009;Li, Wang, and Gatlin 2008;Poppi et al 2011). The slope-ratio is usually determined by linear regression model (y = b1 + b2 9 S + b3 9 T, Sstandard and T-test diets) that needs pre-validation of three basic assumptions: linearity of the responses, common intercepts for all lines, and the equal basal level response to the common intercept (Finney 1951(Finney , 1964Batterham, Murison & Lewis 1979;Littel et al 1997).…”
Section: Discussionmentioning
confidence: 99%